EFEKTIVITAS MODEL PEMBELAJARAN ESCAPE DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI - Putu Ayu Paramita Dharmayanti; Ni Luh Ketut Sri Widhiasih (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
This study aims to determine the effectiveness of ESCAPE learning model. The research conducted is Class Action Action Research (CAR) / Classroom Action Research (CAR). The data were collected using a writing test. Subjects in this study were high school students (SLUA) ​​Saraswati 1 Denpasar academic year 2016/2017. In order to obtain the necessary results in data collection used valid instrument and reliable form of test. The data taken in this study were obtained from Pre-test and Post-test made by the researcher. The data obtained will be analyzed by comparing the level of percentage improvement of writing ability of English description essay starting from pre-test value until post-test. From the result of pre-test and post-test value that have been analyzed can be seen that skill of writing description essay at each meeting is increasing. It can be concluded that ESCAPE learning model is effective to improve students' writing skill especially description essay. This is because the ESCAPE learning model has several advantages that have a specific learning stages and is a student-centered learning.